Variations in the Magnetic Properties of Meteoritic Cloudy Zone - Claire I. O. Nichols; James F. J. Bryson; Roberts Blukis; Julia Herrero‐Albillos; Florian Kronast; Rudolf Rüffer; Aleksandr I. Chumakov; Richard J. Harrison (Geochemistry, Geophysics, Geosystems, 2020)
Abstract Iron and stony‐iron meteorites form the Widmanstätten pattern during slow cooling. This pattern is composed of several microstructures whose length‐scale, composition and magnetic properties are dependent upon cooling rate. Here we focus on the cloudy zone: a region containing nanoscale tetrataenite islands with exceptional paleomagnetic recording properties. We present a systematic review of how cloudy zone properties vary with cooling rate and proximity to the adjacent tetrataenite rim. X‐ray photoemission electron microscopy is used to compare compositional and magnetization maps of the cloudy zone in the mesosiderites (slow cooling rates), the IAB iron meteorites and the pallasites (intermediate cooling rates), and the IVA iron meteorites (fast cooling rates). The proportions of magnetic phases within the cloudy zone are also characterized using Mössbauer spectroscopy. We present the first observations of the magnetic state of the cloudy zone in the mesosiderites, showing that, for such slow cooling rates, tetrataenite islands grow larger than the multidomain threshold, creating large‐scale regions of uniform magnetization across the cloudy zone that render it unsuitable for paleomagnetic analysis. For the most rapidly cooled IVA meteorites, the time available for Fe‐Ni ordering is insufficient to allow tetrataenite formation, again leading to behavior that is unsuitable for paleomagnetic analysis. The most reliable paleomagnetic remanence is recorded by meteorites with intermediate cooling rates ( ∼ 2–500 °C Myr −1) which produces islands that are “just right” in both size and degree of Fe‐Ni order.